Memprediksi Pola Ban Hero Pada Game Mobile Legends Menggunakan Algoritma Apriori - Jordy Lasmana Putra; Syarah Seimahuira (LPPM Universitas Bina Sarana Informatika, 2021)
In this digital era, the development of video games is so rapid, from console-based to smartphone devices. One of the trending video game genres is the Multiplayer Online Battle Arena (MOBA) with one of the most popular MOBA games, the Mobile Legends game. In winning a match in a Mobile Legends game, a good game strategy is needed from each team to defend the base and destroy the opponent's base, one of which is by Ban Hero or banning some existing heroes so that they cannot be used both for the opposing team and for the opposing team. own team. Therefore, this study was conducted to predict the pattern of hero tires using the Apriori algorithm which was carried out on 9 attributes of Hero Mobile Legends. From the results it is known that CHOU Hero is more widely used and not banned compared to 8 other Heroes